Guidelines for Developing the Efficiency of the Electronic Land Office’s Land Registration System and Legal Transactions in Roi Et Province: Guidelines for Developing the Efficiency of the Electronic Land Office’s Land Registration System and Legal Transactions in Roi Et Province - Junphiw, Nakkanun; Promphoonga, Jirapon (RATANABUTH JOURNAL, 2026)
The objectives of this mixed-methods research were to: 1) examine the efficiency level of using the electronic land registration and legal acts system; 2) investigate the problems and obstacles in developing its efficiency; and 3) explore guidelines for developing the efficiency of using the electronic land registration and legal acts system at the Electronic Land Office in Roi Et Province. The sample consisted of 352 service recipients and officials in Roi Et Province, determined using Taro Yamane’s formula. Data collection instruments included a 5-point Likert scale questionnaire and in-depth interviews with 15 key informants. Quantitative data were analyzed using mean and standard deviation, while qualitative data were analyzed using interpretive and content analysis. The research findings revealed that: 1) The overall efficiency level of using the electronic land registration and legal acts system at the Electronic Land Office in Roi Et Province was at a high level (= 3.97, S.D. = 1.00).2) Regarding the problems and obstacles, it was found that personnel lacked expertise in information technology systems. Furthermore, there was a lack of information network stability, excessive complexity in system workflows, and a lack of digital literacy and familiarity among service recipients with digital platforms. 3) Guidelines for efficiency development included organizing training programs to upskill and reskill personnel in digital competencies, upgrading network infrastructure to enhance stability, and optimizing system software to support full-scale e-service operations. Additionally, dedicated helpdesk staff should be stationed to assist citizens, and administrative procedures should be streamlined to enhance user-friendliness.